Big changes in management of food processing information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The traditional sources of information on small-scale food processing have been commercial (the manufacturers of equipment) and the information networks which operate question-and-answer services (QAS). Most QAS are now organised nationally and...